Factors Causing The Decline In Revenue Of KMP Raja Dilaut Before COVID-19 Until Pandemic Recovery - Arif Fuddin Usman; Andi Nur Alimah; Andi Murtafiah; Rusnaedi; Rifkah Fitriah (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
This research is to determine and compare KMP. Raja Dilaut income before COVID-19, during COVID-19, and the pandemic recovery period, as well as the factors causing the decline. KMP. Raja Dilaut is one of the crossing vessels owned by PT Pelayaran Nusantara Juli Rahayu which operates at the Bajoe-Kolaka Ferry Port. The purpose of this research is: 1) to determine KMP. Raja Dilaut income before, during, and during the COVID-19 recovery period, from 2018 to 2022, 2) to determine the factors causing the decline and increase in income KMP. Raja Dilaut. This research is qualitative research using interactive model data analysis techniques, starting from the data collection stage followed by data reduction, data display, and the final stage, namely the conclusion. KMP. Raja Dilaut income recap calculation results from 2018 worth